2018
DOI: 10.1002/maco.201810263
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of corrosion rate measurement techniques applied to reinforcing steel in concrete

Abstract: This paper presents an investigation of five corrosion‐monitoring techniques for reinforced concrete. The techniques studied are the potentiodynamic, galvanostatic, and coulostatic direct‐current techniques as well as electrochemical impedance spectroscopy (EIS), and the connectionless electrical pulse response analysis (CEPRA) technique. The study included monitoring corrosion rates on reinforced concrete specimens with a range of admixed chloride percentages, cover depths, and rebar diameters for 8 months. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…i corr is the CCD, μAÁcm −2 . B is Stern-Geary constant ranged from 13 to 52 mV [36][37][38] ; B value of 26 mV is suitable for the corroded rebar, whereas B value of 52 mV is used for uncorroded rebar, 39 and the criteria for evaluating the corrosion degree of rebar was given in Reference 31.…”
Section: Experimental Principlementioning
confidence: 99%
“…i corr is the CCD, μAÁcm −2 . B is Stern-Geary constant ranged from 13 to 52 mV [36][37][38] ; B value of 26 mV is suitable for the corroded rebar, whereas B value of 52 mV is used for uncorroded rebar, 39 and the criteria for evaluating the corrosion degree of rebar was given in Reference 31.…”
Section: Experimental Principlementioning
confidence: 99%
“…It has been reported that in appraisal of the state of passivity of reinforcement, a more accurate estimate of passive corrosion rates can be achieved by using slower scan rates . Therefore, conforming to ASTM G5, the LPR test was carried out at a fixed scan rate of 0.166 m V −1 s −1 .…”
Section: Experimental Programmentioning
confidence: 99%
“…This method uses a low‐range potential similar to that used in linear polarization resistance test, so electrochemical impedance spectroscopy is considered as a non‐destructive method. The cycles of potentials used in this method vary from anodic to cathodic values ​​and unlike the methods described above, are produced from alternating current instead of direct current . Using a low potential range in this test, results in minimum disturbance in the electrochemical system that reduces the errors caused by the measurement.…”
Section: Experimental Programmentioning
confidence: 99%
“…Various electrochemical methods (potential mapping, galvanostatic pulse, electrochemical impedance spectroscopy, potentiodynamic polarization measurements) are used for the corrosion monitoring of steel in concrete [22][23][24][25][26], but their interpretation can be difficult and, in some cases, unreliable. The specific feature of corrosion in concrete is that the anodic and cathodic sites are spatially localized due to the porous structure of the concrete [5], while the porosity of the concrete also affects the transport of the electrolyte and oxygen, determining the dynamics of the corrosion processes [27].…”
Section: Introductionmentioning
confidence: 99%